Enhancing Postgraduates’ English Communication Competencies through Experiential Learning - Han, Hongmei; Huo, Yuguang; Zhang, Li (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
English communication competencies are increasingly crucial for academic and professional success. However, many non-English major postgraduate students in China struggle with effectively communicating in English as a foreign language (EFL). This study aims to examine whether experiential learning can make a difference to these student’ English communication competencies. A mixed-method approach was employed, with data collected from 178 postgraduate students at a Chinese university, through pre- and post-intervention surveys and student feedback reports. Quantitative data were analyzed using descriptive statistics and paired-samples t-tests, while qualitative data were coded and analyzed thematically. The results showed significant improvements in the students’ communication competencies, with qualitative findings highlighting the role of the instructor, group dynamics, content focus, and learning environment. The study demonstrates great potential of experiential learning for the enhancement of EFL communication competencies.